The Relationship Between Relational Quality and Megaproject Success: The Moderating Role of Incentives. Issue 4 (2nd October 2019) - Wang, Dedong; Fu, Hongwei; Fang, Shaoze
Abstract: To improve the success rate of megaprojects from a relational perspective, we analyzed the factors that affect relational quality in megaprojects and the impact of relational quality on megaproject success. Based on survey data from 172 respondents, partial least squares structural equation modeling (PLS-SEM) was used to test the proposed structural model. The results show that in the case of low-level incentives, asset specificity and uncertainty have a negative impact on relational quality. Further, goodwill-based trust, competence-based trust and dependence have a positive effect on relational quality. However, in the case of high-level incentives, the negative impact of uncertainty on relational quality disappears, and the effect of asset specificity on relational quality becomes positive. In addition, this study validates the role of relational quality in promoting megaproject success; surprisingly, the moderating role of incentive level is not significant. These findings can help project managers improve megaproject success with the relational method and provide an inspiration for engineering managers to re-evaluate the effectiveness of incentives.